Exploring effective methods of conflict resolution: Strategies and challenges for sustainable peace - Bora, Aman; Kumar, Ajay; Dwivedi, Akhilesh (The Scientific Temper, 2025)
Conflicts persistently present substantial risks to worldwide peace and stability, thus requiring the implementation of efficient settlement strategies. The challenges include cultural boundaries, power dynamics, economic conflicts, involvement of non-state actors, and humanitarian considerations, which make the resolution efforts more difficult. This chapter examines various tactics, obstacles, and consequences of conflict resolution to achieve long-lasting peace. It defines fundamental concepts and viewpoints in conflict resolution, which then guide further investigations. The chapter examines diplomatic negotiation, mediation, peacebuilding initiatives, and legal mechanisms as essential tools backed by empirical data and case studies. This research enhances conflict resolution approaches essential for global peace and security by combining theoretical insights with facts.